2014
DOI: 10.1038/jid.2014.61
|View full text |Cite
|
Sign up to set email alerts
|

IL-9 Regulates Allergen-Specific Th1 Responses in Allergic Contact Dermatitis

Abstract: The cytokine IL-9, derived primarily from T-helper (Th)-9 lymphocytes, promotes expansion of the Th2 subset and is implicated in the mechanisms of allergic asthma. We hypothesize that IL-9 also plays a role in human allergic contact dermatitis (ACD). To investigate this hypothesis, skin biopsy specimens of positive patch test sites from non-atopic patients were assayed using qPCR and immunohistochemistry. Along with Th2 associated cytokines, IFN-γ, IL-4, and IL-17A, expression of IL-9, and PU.1, a Th9-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
60
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 36 publications
0
60
1
4
Order By: Relevance
“…39 Alternately, higher Th9 frequency in adults versus children with AD may be attributed to higher allergic contact dermatitis seen in this group, though this is speculative. 102 …”
Section: Discussionmentioning
confidence: 99%
“…39 Alternately, higher Th9 frequency in adults versus children with AD may be attributed to higher allergic contact dermatitis seen in this group, though this is speculative. 102 …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed a T-cell subset (Th9 cells) that predominantly produces IL-9 and is distinct from the classic Th1, Th2 and Th17 subsets (2-4). Several reports showed that Th9 cells could be involved in the pathogenesis of chronic allergic disorders such as asthma, allergic rhinitis and atopic dermatitis (23,24). Further studies indicated that serum levels of IL-9 are increased in patients with SLE and other autoimmune diseases such as systemic scleroderma (8,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Blister fluid was aspirated at the 48-or 72-hour readings and studied for IL-9 content using an IL-9Yspecific enzyme linked immunosorbent assay. 3 High levels of IL-9 were identified in all 5 ACD specimens (1589 T 459 pg/mL; n = 5). In addition, we measured IL-9 levels in 3 normal human serum controls and blister fluid from 3 different control blistering skin diseases: an ischemic blister, an edema blister, and bullous pyoderma gangrenosum (PG).…”
mentioning
confidence: 98%
“…Surprisingly, irritant contact dermatitis was impaired in IL-9 j/j mice compared with wild-type mice, suggesting a role for IL-9 in promoting an inflammatory response during contact dermatitis. 3 This prompted us to study IL-9 production in extreme cases of ACD at the protein level (ex vivo).…”
mentioning
confidence: 99%